Penemuan Bangsa Melayu - Jajat Burhanudin (Studia Islamika, 1996)
This work discusses the process of inventing politics by Malay society, with special attention to the debate and contest of three ideological orientations which have emerged within the society since British colonialization. Tese three ideological orientations arae Kerajaan, Kebangsaan, and Islam. They have been involved in the struggle and the debate concerning the attempt to formulate the community and identity of Malay society, the principles of social organization, and the way individuals are perceived.DOI: 10.15408/sdi.v3i4.797